2020
DOI: 10.1080/09243453.2020.1830125
|View full text |Cite
|
Sign up to set email alerts
|

Back on track? How civic learning opportunities widen the political knowledge gap in a tracked education system

Abstract: This article examines how different civic learning opportunities relate to students' political knowledge in different school tracks. Existing studies found out that citizenship teaching can not only enhance overall levels of civic outcomes but also mitigate inequalities. However, educational achievement studies emphasise the risk of a tracked school context exacerbating the general knowledge gap. Combining these findings, we do not know whether efforts in the vocational track to enhance civic outcomes can stil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
2
6
0
Order By: Relevance
“…Data from the International Citizenship and Education Study (ICCS) 2016 revealed that in all participating countries, students’ perceptions of an open classroom climate were on average positively associated with students’ political knowledge and political interest (Schulz et al, 2018 ). Similar findings were reported for predecessor studies (Schulz et al, 2009 ; Torney-Purta et al, 2001 ).…”
Section: Introductionsupporting
confidence: 89%
“…Data from the International Citizenship and Education Study (ICCS) 2016 revealed that in all participating countries, students’ perceptions of an open classroom climate were on average positively associated with students’ political knowledge and political interest (Schulz et al, 2018 ). Similar findings were reported for predecessor studies (Schulz et al, 2009 ; Torney-Purta et al, 2001 ).…”
Section: Introductionsupporting
confidence: 89%
“…In the 21st century learning paradigm, education is characterized by differences in learning orientation, where there must be an educational interaction between teachers and students to achieve learning goals (Conklin, 2009;Scott, 2014) The learning process must be directed at the formation of creative, innovative, and characterized students in the digital era by utilizing technological advances and digital media, from the opinions of experts and research results (Conklin, 2009;Gallardo-Echenique et al, 2015;Scott, 2014). it can be understood that civic education learning in the development of 21 st century education, especially online learning, is able to provide a meaningful role, such as making students more active than before, digital media literacy, critical thinking, creative and innovative in learning or when preparing students to become teachers who are able to fight digital adaptation in the future (Biamba et al, 2021;Dias & Soares, 2018;Sampermans et al, 2021;Wong et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we adjusted the time span to include only studies from 2000 onward, excluding Hoffer (1992). Other examples of exclusion concern studies that do not cover the population of interest (secondary school students) but focus on primary school students (e.g., Duflo et al, 2011; Sterbinsky et al, 2006); studies that measure the impact of attending a specific track (e.g., Pop-Eleches & Urquiola, 2011; Van Houtte et al, 2013) instead of the overall effect of tracking as a system-level characteristic; studies whose dependent variable was not cognitive achievement or student performance but, for instance, noncognitive skills or educational transitions (e.g., Guyon et al, 2012; Sampermans et al, 2021); and studies that address different research questions and/or employ a non comparable analytical design (Banerjee, 2017; Beattie, 2017; Mickelson & Everett, 2008).…”
Section: Methodsmentioning
confidence: 99%